SCIENTIFIC ORGANIZATION OF THE ACTIVITIES OF EMERGENCY EXPERT AND ACCIDENT REPORTING SERVICE DEPARTMENTS - Ибрагимов Икромжон Саидахметович; Райимов Сабиржан Задибекович; Шодиев Ғофур Баратович; Махматмуродов Фарход Хайдарович (Web of Journals Publishing, 2025)
In this article the problems that are depend on the function of “ Operative forensic and the section that services to notify the accidents” were discussed. Creating of new normative documents that are mark the activity service and modern methods of scientific organizational work were offered.
Keywords: Informing accidents, appeal of citizens, unknown corpses.